2016
DOI: 10.17795/ijpbs-4983
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Solution-Focused Therapy on Married Couples’ Burnout

Abstract: Background: Couple burnout results from plethora of non-realistic expectations, irrational thoughts, past awareness and understanding of each other's needs and wide difference of couples past expectations and reality. Objectives: The present research was conducted to investigate the effectiveness of solution-focused therapy on couple burnout among couples referred to Shahryar city court for divorce. Materials and Methods:The population included all couples referred to this court during the month of May, 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results of Padash's study showed that educational intervention based on the couple therapy causes a significant reduction in marital burnout in the experimental group and also reduces the rate of divorce among married women [32]. The results of a study showed that solution-focused therapy intervention reduced the rate of marital burnout in the experimental group and improved their marital quality [33]. Implementing pre-marital or post-marital education programs has a positive effect on the quality of life and marital satisfaction of couples and reduces their marital burnout [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Padash's study showed that educational intervention based on the couple therapy causes a significant reduction in marital burnout in the experimental group and also reduces the rate of divorce among married women [32]. The results of a study showed that solution-focused therapy intervention reduced the rate of marital burnout in the experimental group and improved their marital quality [33]. Implementing pre-marital or post-marital education programs has a positive effect on the quality of life and marital satisfaction of couples and reduces their marital burnout [34][35][36].…”
Section: Discussionmentioning
confidence: 99%